Hunger and overweight in Canadian school-aged children: A propensity score matching analysis - Sentenac, Mariane (Can J Public Health, 2016)
OBJECTIVE: The last decade saw a higher prevalence of overweight reported among food-insecure families in Canada, but no robust evidence exists on the covariate-adjusted association in children. In this study, we examined the association between hunger and overweight in Canadian students, using a propensity score matching analysis to reduce confounding. METHODS: This research used data from the 2009/2010 Canadian Health Behaviour in School-aged Children study on a representative national sample of students in Grades 6 through 10. Students self-reported their height and weight and how often they have gone to school or to bed hungry due to a lack of food at home. Multivariate logistic regression modeling was conducted on the total sample (N = 17,694) and on the sample matched on propensity scores (n = 7,788). RESULTS: The overall prevalence of overweight among students was 20.2% with a significant difference between students who reported hunger (24.0%; 95% CI: 22.1–26.0) and students who did not (19.0%; 95% CI: 17.9–20.2). Analysis on the matched sample revealed a significant association between hunger and overweight in children (adjusted odds ratio: 1.30; 95% CI: 1.12–1.50). CONCLUSIONS: A substantial number of Canadian students have reported being hungry because of a lack of food at home. These students are at increased risk of overweight, regardless of their social class. Child hunger and household food insecurity exist in Canada and constitute a call for policy action at a national level.